PENERAPAN GAMIFIKASI CLASH OF CHAMPIONS UNTUKMENINGKATKAN KEMAMPUAN BERHITUNG BILANGAN CACAH KELASIV SD - Aisah Nadia Larasati; Pratiwi Kartika Sari; Intan Trisila (JRPD (Jurnal Riset Pendidikan Dasar), 2025)
Learning mathematics in elementary schools requires a creative and innovative approach so that students can more easily understand concepts and be motivated in the learning process. Along with the development of technology and the demands of 21st century learning, educators are required to integrate methods that can increase students' active participation. This study aims to apply gamification-based digital media through the Clash of Champions application to improve the counting ability of grade IV students at SDN Serua 01. This class action research was conducted in two cycles involving 29 students as subjects. Data collection techniques were carried out through observation and assessment. The results showed a significant improvement in students' counting ability. The percentage of students who reached the minimum completion criteria increased from 51.7% at pre-cycle to more than 75% at the end of the second cycle. In addition, the average student score increased from 65.31% at pre-cycle, to 73.41% at cycle I, and reached 84.45% at cycle II. These findings suggest that the application of gamification in learning can be an effective alternative to improve learning outcomes and student engagement in the math classroom. Thus, the use of interactive digital media such as Clash of Champions can be a relevant learning strategy in facing today's educational challenges.